Climate change and trade on the road to Copenhagen ICTSD global platform on climate change, trade policies and sustainable energy - International Centre for Trade and Sustainable Development (ICTSD programme on trade and environment, policy discussion paper, 2008)
The global effort to address climate change will require a fundamental transformation of our economies and the ways we use energy. The current phase of negotiations under the UN Framework Convention on Climate Change (UNFCCC) is set to lay the groundwork for the necessary policy reform, and will require concerted and cooperative efforts by individual countries, the business sector and civil society. Innovation ? both with regard to the technologies of the future and the regulatory frameworks used to usher them in at the scale needed ? will be key to success.